IDENTIFICATION OF KEY NITROGEN USE EFFICIENCY-RELATED GENES IN OIL PALM USING BIOINFORMATICS APPROACHES - Permatasari, Galuh Wening; Setiowati, Retno Diah; Wening, Sri (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Efficient nitrogen use is crucial for maximizing oil palm yield while reducing environmental impact. Poor nitrogen utilization causes excessive growth and nutrient loss. This study uses bioinformatics to identify key genes linked to nitrogen use efficiency, providing insights for genetic improvement and sustainable cultivation.Protein-protein interaction (PPI) networks, functional enrichment, and structural modeling were employed to uncover candidate genes regulating nitrogen uptake and metabolism. Sixty-two nitrogen use efficiency associated genes from rice (Oryza sativa) were analyzed via BLASTp against the E. guineensis genome (NCBI), selecting those with >80% similarity. PPI networks were constructed using STRING-db and analyzed in Cytoscape v3.7.1. Functional enrichment (Gene Ontology) and structural analysis (AlphaFold, PyMol v2.5.4) were performed. Twelve nitrogen use efficiency related genes were identified, with CESA4, CESA7, and CESA9 emerging as key regulators based on high degree and betweenness values in PPI analysis. These genes are linked to plant cell wall biosynthesis. Structural analysis showed high similarity to rice homologs, with RMSD values of 0.338 Å (CESA4) and 0.396 Å (CESA9), indicating strong conservation area. Their structural relevance suggests they are promising targets for molecular breeding marker to enhance nitrogen utilization and sustainability in oil palm.